(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article aims to present the set of books and authors that served as triggers for the creation process of Fúria, a 2018 piece by Lia Rodrigues Companhia de Danças, and the relationship between dance and text that occurs in the choreographer’s creations. Scenes from the piece and their connections with works by authors linked to Afro-Brazilian and Afro-diasporic culture, such as Achille Mbembe, Ana Maria Gonçalves and Conceição Evaristo, are analyzed. The influence of Mário de Andrade’s Macunaíma: o herói sem nenhum caráter (Macunaíma: the hero without any character) on the choreographic work’s continuous flow rhythm is also discussed.